2016
DOI: 10.1177/0379572116676427
|View full text |Cite
|
Sign up to set email alerts
|

Combining Home Garden, Poultry, and Nutrition Education Program Targeted to Families With Young Children Improved Anemia Among Children and Anemia and Underweight Among Nonpregnant Women in Nepal

Abstract: The EHFP intervention improved anemia among children aged 12 to 48 months and their mothers in Baitadi District of Nepal. The intervention also reduced underweight among these women, but had no impact on child growth, in this district.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
68
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 26 publications
14
68
2
1
Order By: Relevance
“…Home garden interventions usually integrate training in gardening techniques (e.g., use of quality seed, planting bed preparation, crop rotation, compost making and pest and disease management) with nutrition education aimed at transferring nutrition knowledge (e.g., which crops contain which essential nutrients) and nutrition skills (e.g., how to prepare food to maintain nutrients) (World Vegetable Center 2016). Outside support is usually provided for one year and only in exceptional cases for a period up to three years (Osei et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Home garden interventions usually integrate training in gardening techniques (e.g., use of quality seed, planting bed preparation, crop rotation, compost making and pest and disease management) with nutrition education aimed at transferring nutrition knowledge (e.g., which crops contain which essential nutrients) and nutrition skills (e.g., how to prepare food to maintain nutrients) (World Vegetable Center 2016). Outside support is usually provided for one year and only in exceptional cases for a period up to three years (Osei et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that integrated home garden interventions are effective in increasing the consumption of nutritious food among poor rural households in developing countries (Olney et al 2009(Olney et al , 2013Schreinemachers et al 2016;Tesfamariam et al 2018;Osei et al 2017). Several recent reviews have identified that such interventions are one of few agricultural interventions with a proven impact on increased vegetable consumption, although the evidence basis for nutritional status remains weak (DFID 2014;Ruel et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few livestock rearing intervention studies that have assessed impacts on anaemia or haemoglobin (Hb) concentrations among women or children were implemented in combination with other interventions, thus obfuscating the independent role of livestock. These interventions, introducing small-scale, homestead poultry production in concert with promotion of vegetable gardens, field crop production, and/or provision of nutrition education, have shown mixed impacts on anaemia (Galal, Harrison, Abdou, & Zein el Abedin, 1987;Olney, Pedehombga, Ruel, & Dillon, 2015;Olney, Talukder, Iannotti, Ruel, & Quinn, 2009;Osei et al, 2016). The scant observational evidence for the association of livestock rearing with anaemia has similarly shown mixed results with studies reporting higher (Ahenkorah, Nsiah, & Baffoe, 2016;Iannotti et al, 2015) and lower (Flores-Martinez, Zanello, Shankar, & Poole, 2016;Miller, 2010) odds of anaemia associated with livestock rearing.…”
mentioning
confidence: 99%
“…Of the remaining, nine occurred in India (Alive & Thrive India, n.d.; Bhandari et al, ; Bhandari et al, ; Dongre, Deshmukh, & Garg, ; Kadiyala, Morgan, Cyriac, Margolies, & Roopnaraine, ; Kilaru, Griffiths, Ganapathy, & Ghosh, ; Palwala et al, ; Singh et al, ; Vazir et al, ) and eight Central/South American or Mexico (Bonvecchio, Pelto, Escalante, & Monterrubio, ; de Oliveira, Giugliani, Santo, & Nunes, ; Iannotti et al, ; Jensen, Frongillo, Leroy, & Blake, ; Leroy et al, ; Monterrosa et al, ; Penny et al, ; Santos et al, ). Five were implemented in China (Guldan et al, ; Li et al, ; Sun et al, ; J. Zhang, Shi, Chen, Wang, & Wang, ; Y. Zhang et al, ); three in Vietnam (Bruyeron et al, ; Dickey et al, ; Nguyen et al, ); two each in Cambodia (Olney, Talukder, Iannotti, Ruel, & Quinn, ; Reinbott et al, ) and Nepal (Cunningham et al, ; Osei et al, ); and one each in Indonesia (S. White et al, ), Pakistan (Zaman, Ashraf, & Martines, ), and Egypt (Brasington et al, ). Target reach ranged from less than 1,000 for smaller scale research and pilot programs to over one million targeted for large‐scale, government‐implemented programs (i.e., Madagascar and India).…”
Section: Resultsmentioning
confidence: 99%